Procedural Fairness in Restructuring and Layoffs between two Telecom Companies of Pakistan - Hussain, Jibran; Ali, Hassan; Sadik, Mobashar; Qasim, Saba (Global Journal of Social Sciences Studies, 2017)
This study compares impact of Procedural Fairness in Layoffs and Restructuring on Employee satisfaction between two telecom companies [Pakistan Telecommunication Company Limited (PTCL) and Nokia Siemens Network (NSN)] operating in Pakistan. An instrument is developed to collect data, through convenient based nonprobability sampling, whereas, sample size of the target audience is determined through Power and Precision method. Correlation coefficient shows strong positive association between Procedural Fairness in Restructuring and Layoffs with Employee Satisfaction in case of NSN then PTCL. Moreover, regression analysis show that Procedural Fairness in Restructuring and Layoffs are fairer in case of NSN as compare to PTCL. These processes have matured in case of NSN, where employees are more satisfied with the Procedural Fairness in Layoffs than Restructuring. Whereas, employees are not or least satisfied with the Procedural Fairness in Restructuring and found these procedures as shock in case of PTCL, with the least satisfactory level.